Srampangan – Sadumuk Saunine Untuk Meningkatkan Motivasi dan Hasil Belajar Siswa Tentang Basa Ngoko-Krama Inggil Bahasa Jawa - Agung Vendi Setyawan (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2018)
The research objectives were to improve the fifth-grade children’s motivation and speaking competency in using the Basa Kromo Inggil speech level in Javanese in public school Tamanan 2 Kalasan. A classroom action research was implemented in two cycles using SRAMPANGAN game with card media scaffolded with slippers. Data were collected through learning Javanese with Basa Kromo Inggil speech level. The obtained data were analyzed descriptively and quatitatively. Research results show that children’s learning motivation in Javanese with Basa Kromo Inggil speech level was improved to 55.71%. While, the children’s competency in speaking Javanese with Basa Kromo Inggil speech level was also improved to 60% in cycle 1 and 90% in cycle 2. The learning processes and outcomes are also meant to conserve the Javanese cultural assets.